Strategies to Increase Representation of Students with Disabilities in Science, Technology, Engineering and Mathematics (STEM) - Jeffry L. White; G.H. Massiha (Institute of Advanced Engineering and Science, 2015)
As a nation wrestles with the need to train more professionals, persons with disabilities are undereducated and underrepresented in science, technology, engineering, and mathematics (STEM). The following project was proposed to increase representation of students with disabilities in the STEM disciplines. The program emphasizes an integrated program of interventions for college students with disabilities (SwD) majoring in STEM which centers on a system of continuous student monitoring with rapid access to academic and personal services, as well as professional development and degree enhancing experiences supplied during the entire period of college attendance.